Evaluation of graft effluent high mobility group box-1 (HMGB-1) for prediction of outcome after liver transplantation - Houben, Philipp; Hohenberger, Ralph; Yamanaka, Kenya; Büchler, Markus W.; Schemmer, Peter (Annals of transplantation, 2018)
BACKGROUND: Pre-transplant assessment of the graft for liver transplantation is crucial. Based on experimental data, this study was designed to assess both nuclear high mobility group box-1 (HMGB-1) protein and arginine-specific proteolytic activity (ASPA) in the graft effluent. MATERIAL AND METHODS: In a non-interventional trial, both HMGB-1 and ASPA were measured in the effluent of 30 liver grafts after cold storage before transplantation. Values of HMGB-1 and ASPA levels were compared with established prognostic parameters such as the donor risk index, balance of risk score, and Donor-Model for End-Stage Liver Disease.RESULTS: The early allograft dysfunction (EAD) was best predicted by recipient age (p=0.026) and HMGB-1 (p=0.031). HMGB -1 thresholds indicated the likelihood for initial non-function (1608 ng/ml, p=0.004) and EAD (580 ng/ml, p=0.017). The multivariate binary regression analysis showed a 21-fold higher (95% CI: 1.6-284.5, p=0.022) risk for EAD in cases with levels exceeding 580 ng/ml. The ASPA was lower in cases of initial non-function (p=0.028) but did not correlate with the rate of EAD (p=0.4). CONCLUSIONS: This study demonstrates the feasibility of HMGB-1 detection in the graft effluent after cold storage. Along with conventional prognostic scores, it may be helpful to predict the early fate of a graft in human liver transplantation.
Gesehen am 30.07.2018